2013
DOI: 10.1080/17429145.2012.680077
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of endophytic bacteria fromPlectranthus tenuiflorusmedicinal plant in Saudi Arabia desert and their antimicrobial activities

Abstract: The diversity and beneficial characteristics of endophytic microorganisms have been studied in Plectranthus tenuiflorus medicinal plant. However, information regarding naturally occurring P. tenuiflorus plant associated endophytes among different organs of host is limited. Endophytic bacteria were isolated from root, stem, and leaves of P. tenuiflorus plant. Among 28 endophytic bacterial isolates from different organs of P. tenuiflorus plant, 8 isolates were identified by partial sequencing of their 16S rRNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
58
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(65 citation statements)
references
References 59 publications
2
58
1
4
Order By: Relevance
“…The result of BLAST analysis along with accession number of submitted 16S rDNA sequence of purified bacteria is summarized as Table 1. The isolates ZB1 to ZB5 showed maximum identity to Bacillus sp. El-Deeb et al, (2013) reported the isolation of 28 endophytic bacterial isolates from different organs of P. tenuiflorus plant, which belonged to Bacillus sp., Bacillus megaterium, Bacillus pumilus, Bacillus licheniformis, Micrococcus luteus, Paenibacillus sp., Pseudomonas sp., and Acinetobacter calcoaceticus. De Oliveira Costa et al reported that (de Oliveira Costa et al, 2012) 23 different genera were isolated from common bean (Phaseolus vulgaris).…”
Section: Isolation and Identification Of Endophytic Bacteria From Z mentioning
confidence: 99%
“…The result of BLAST analysis along with accession number of submitted 16S rDNA sequence of purified bacteria is summarized as Table 1. The isolates ZB1 to ZB5 showed maximum identity to Bacillus sp. El-Deeb et al, (2013) reported the isolation of 28 endophytic bacterial isolates from different organs of P. tenuiflorus plant, which belonged to Bacillus sp., Bacillus megaterium, Bacillus pumilus, Bacillus licheniformis, Micrococcus luteus, Paenibacillus sp., Pseudomonas sp., and Acinetobacter calcoaceticus. De Oliveira Costa et al reported that (de Oliveira Costa et al, 2012) 23 different genera were isolated from common bean (Phaseolus vulgaris).…”
Section: Isolation and Identification Of Endophytic Bacteria From Z mentioning
confidence: 99%
“…IN recent years, there is increasing interest regarding plant-microbe association, particularly in composition, structure and function of endophytic bacteria 1 that colonize plants without apparently causing any damage 2 . Endophytes establish a mutualistic symbiosis with their hosts because they are selectively favoured 3,4 .…”
mentioning
confidence: 99%
“…Endophytes stimulate plant growth through several mechanisms such as nitrogen fixation, inorganic phosphate solubilization, siderophore production, micronutrient supply 6 , photosynthetic activity and phytostimulation 5 . Endophytic bacteria can also contribute to soil pathogen control with the production of antibiotics and secondary metabolites and induction of the plant defence system 3 , besides heavymetal biotransformation, biodegradation of organic pollutants 2 , osmotic adjustment, stomatal regulation, modification of the root morphology and metabolism 1 . Jojoba (Simmondsia chinensis) is a shrub native to northwestern Mexico and southwestern United States.…”
mentioning
confidence: 99%
See 2 more Smart Citations